Peculiarity of older patients’ pharmacotherapy - Pruszyński, Jacek J. (Przewodnik Lekarza/Guide for GPs, 2009)
Because of ageing process which appears in the senior population, the pharmacokinetics and pharmacodynamics of medicines change. It is connected, inter alias with: growth of fat tissue in older age, decrease of water content and decline of the concentration of albumin. In the ageing process a decrease of kidney clearance occurs because the function of the kidneys worsens in old age. Pharmakodynamic changes in senior systems are connected to either the decrease or the increase of response on used treatments. The activity of the sympathetic system increases with age, which leads to decline of beta-adrenergic receptors sensibility and to weakening the response to drugs which work through these receptors. Sensibility of alfa-adrenergic receptors doesn’t undergo any major changes, and the dopaminergic sensibility in the central nervous system weakens. Because old age is connected to the progressive declining of adaptive abilities and polipathology which is a widespread seniors’ occurrence, homeostatis is easily disturbed and many unexpected reactions connected to simultaneous usage of various medicines occur. For this reason, seniors’ pharmacotherapy, should be conducted in a well balanced way, which takes into consideration the individual characteristic of every patient.